MODEL KEBIJAKAN DAN SISTEM HUKUM PEMBERANTASAN PEMBALAKAN LIAR DI INDONESIA (STUDI KASUS DI PROVINSI RIAU) - Marissa Grace Haque; Rinekso Soekmadi; Hasim Hasim; Hartrisari Hardjomidjojo; Daud Silalahi (Graduate School Bogor Agricultural University (SPs IPB), 2013)
A high rate and massive illegal logging cases from the past until to date, and the low rate of law compliance in the sense of Indonesia law and policy implementation, awoke some issues that encourage Indonesia and Indonesian jurists to build a better system. Conducting the research from 2005-2007, and thoroughly observing its development until 2011, from as many as 23 Statutory Laws start from the umbrella of the Basic Law or UUD 45 (Undang Undang Dasar 1945), follow with Laws or UU(Undang Undang), Policies or Kebijakan as Government Regulation or PP (Peraturan Pemerintah), Presidential Decree orKEPPRES (Keputusan Presiden), and Presidential Instruction or INPRES (Instruksi Presiden), strive the researcher to scrutinizethem prudently. The research conduction aims to build a model-system that might contribute to the 2012 national accelerationanti-illegal logging movement in Indonesia region.Keywords: Model system, UUD 45, UU, government regulation; PP, presidential decree; KEPPRES, presidential instruction;INPRES